A simple test of the New Keynesian Phillips Curve - Andrea Carriero (Queen Mary University of London, Department of Economics, 2007)
We propose a way to test the New Keynesian Phillips Curve (NKPC) without estimating the structural parameters governing the curve, i.e. price stickiness and firms' backwardness. Using this strategy we can test the NKPC avoiding the identification problems related to the GMM approach. We find that it does not exist a combination of the structural parameters which is consistent with US data. This result does not necessarily imply that the idea of a forward looking price setting behaviour should be entirely disregarded, as the rejection might be due to the failure of the joint hypothesis of rational expectations. Thus further research should be aimed at providing alternative models for agents' expectations.
Keywords: C32; E31; 330; VARs; Inflation; Phillips curve; New-Keynesian Phillips Curve; Inflation; Momentenmethode; VAR-Modell; Theorie; USA